2006
DOI: 10.2214/ajr.04.1785
|View full text |Cite
|
Sign up to set email alerts
|

MRI Appearance of Wrisberg Variant of Discoid Lateral Meniscus

Abstract: The Wrisberg variant of the discoid lateral meniscus is a rare condition with a highly suggestive clinical history. The musculoskeletal radiologist should consider this diagnosis whenever a discoid lateral meniscus is identified because making this elusive diagnosis may prove immensely useful for the orthopedic surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Symptoms of discoid meniscus include insidious popping or snapping without a traumatic origin, which is associated with pain, giving way, effusion, quadriceps atrophy, limited range of motion, and clicking or locking28,34). Snapping knee syndrome, in which a clunk is heard at the end of flexion, is usually related to an unstable meniscus variant, such as the Wrisberg type35,36). In very young children (range, 3 to 4 years), snapping is often asymptomatic, whereas older children (range, 8 to 10 years) more commonly experience pain with activity37).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of discoid meniscus include insidious popping or snapping without a traumatic origin, which is associated with pain, giving way, effusion, quadriceps atrophy, limited range of motion, and clicking or locking28,34). Snapping knee syndrome, in which a clunk is heard at the end of flexion, is usually related to an unstable meniscus variant, such as the Wrisberg type35,36). In very young children (range, 3 to 4 years), snapping is often asymptomatic, whereas older children (range, 8 to 10 years) more commonly experience pain with activity37).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…An abnormal, thickened, bow-tie appearance of the meniscus is suggestive of discoid meniscus28). In the Wrisberg variant, an MRI scan may show subtle anterior subluxation of the posterior horn of the lateral meniscus or high T2-weighted signal intensity, simulating a peripheral tear35). However, some authors have reported low sensitivity in detecting the lateral discoid meniscus in children and have suggested that MRI does not provide enhanced diagnostic utility over clinical examination44) because checking the stability of a discoid meniscus on an MRI scan is difficult, and some incomplete discoid menisci often look normal9,19).…”
Section: Diagnosismentioning
confidence: 99%
“…Discoid menisci are most commonly observed on the lateral side and are more prone to wear and tear (Fig. 6) [19,20].…”
Section: Meniscal Lesions and Variantsmentioning
confidence: 99%
“…MRI can also provide information on intra-substance tissue, meniscal tear, and the presence of associated osteochondritis dissecans. Incomplete, Wrisberg ligament type or unstable, normally shaped, menisci are much more difficult to discern [42]. A ring-shaped meniscus is not easily distinguished from a bucket handle tear of the normal lateral meniscus using MRI [43].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%